SOSIALISASI DAN PENANAMAN NILAI-NILAI MULTIKULTURALISME PADA MAHASISWA PROGRAM STUDI SASTRA INGGRIS UNIVERSITAS HALU OLEO - Nur Israfyan Sofian (Universitas Halu Oleo, 2022)
Multiculturalism in Indonesia is not a new thing. Various ethnic groups from Sabang to Merauke, various languages and dialects make Indonesian people so accustomed to diversity and implement a respectful life with one another. However, it is not uncommon to find an attitude of intolerance in response to the culture of other communities. Community service in socialising and instilling the value of multiculturalism to students of the English Literature Study Program at Halu Oleo University is considered very important to do. This activity was held on 26 June 2022 by presenting two main speakers with 70 participants through the Google Meet application. The method used was by presenting material about Muticulturalism in America which was illustrated one of them through literary works written by people with American citizenship but of Asian, European, African and other blood. Their literary works illustrate the forms of multiculturalism that they not only experience but also tell as it happens around them. This activity is a moment of counselling for UHO English Literature students who will soon complete their education and work in the community.